Estimating the Prevalence of Fungal Nail Infections and Potential Concerns for Central Disease Surveillance Hub in Pakistan - Uppal, Sara Rizwan; Uppal, Rizwan; Khan, Aftab Ahmad; Saeed, Umar; Piracha, Zahra Zahid; Ali, Zuhaib (Archives of Clinical and Biomedical Research, 2022)
Nail fungal infections remained unnoticed during COVID-19 pandemic. Herein, we first-time reported national data acquired from 100 branches of IDC Pakistan against Aspergillus species, Penicillium species, Epidermophyton species, Candida species, Candia albicans, Trichophyton species, Bipolaris species or Unidentified fungal infections. Among 497 participants, 22.22% of infections were of Aspergillus species. However, 4.17% of infections were of Candida species and Epidermophyton. The penicillium and Candida albicans species were prevalent at 2.7% among suspected people. However the prevalence of bipolaris species were 1.38%. The unidentified species were also 1.38% among suspected patients, which is potential point of concern. Our results depicted higher level of nail fungal infections among females as compared to males. There is an urgent need for development of national strategies to monitor fungal infections and designing ways for prevention of fungal disease.